Inclusion of children with sensory loss in non-formal education settings: understanding and addressing some of the challenges and tensions in one local authority in Scotland - Hannah, Elizabeth Fraser Selkirk (Frontiers in Education, 2025)
IntroductionInternationally, there has been a drive toward developing an inclusive and equitable educational system which promotes lifelong learning for all. This is reflected in the United Nations Sustainable Development Goal 4 and its associated targets. The current study focuses on some of the challenges and tensions associated with inclusive practice in non-formal education settings for children and young people with a disability, specifically sensory loss, from the perspective of parents/carers and professionals/volunteers.MethodsA commissioned project, conducted in one local authority in Scotland in 2022, investigated the experiences of children and young people with sensory loss (deaf and/or visual impairment) of participating in activities, in school and in the community, with children with and without sensory loss; the opportunities and challenges associated with engaging in these activities; and the perceived benefits. As part of a larger study which gathered the views of children and young people with sensory loss, a virtual focus group was conducted with two parents/carers who are British Sign Language (BSL) users and a semi-structured interview with a parent who is not a BSL user. Furthermore, a virtual focus group was undertaken with three professionals/volunteers working with children and young people with sensory loss (deaf and/or visual impairment).ResultsFindings from the study highlight some of the tensions associated with inclusion in non-formal education settings.DiscussionThere are implications for practice, such as awareness raising for peers and adults; offering more opportunities for children and young people to mix socially with their peers in accessible and well-resourced environments outside school; the importance of seeking children's views about the non-formal activities they like to participate in; and the importance of raising awareness of the benefits for children and young people with sensory loss of being with others with sensory loss. Although the research was conducted in one locality in Scotland, the insights are relevant to an international audience.